2012
DOI: 10.1007/s10368-012-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy and real estate prices: a disaggregated analysis for Switzerland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Moreover, all find evidence that monetary policy influences house prices. A recent study for Switzerland by Berlemann and Freese (2013) analyzes the link between interest rates, house prices and stock prices. Other studies focus on the effect of other macroeconomic variables on house prices.…”
Section: Theoretical Considerations About the Datamentioning
confidence: 99%
“…Moreover, all find evidence that monetary policy influences house prices. A recent study for Switzerland by Berlemann and Freese (2013) analyzes the link between interest rates, house prices and stock prices. Other studies focus on the effect of other macroeconomic variables on house prices.…”
Section: Theoretical Considerations About the Datamentioning
confidence: 99%
“…While the impulse responses decline from their peak effects (which are observed after one 22 Such a persistence in responses has repeatedly been reported in the literature. Berlemann and Freese (2013) find that interest rate effects on different kind of housing are rather persistent, and lose their significance 3-4 years after the shock. The peak effect in levels is reached after 2 years.…”
Section: Time Variationmentioning
confidence: 84%
“…4 Using vectorautoregressions on a sample ranging from 1987, Berlemann and Freese (2013 find that positive interest rate shocks have adverse effects on house and condominium prices. They provide a nice overview of the Swiss real estate market.…”
Section: Introductionmentioning
confidence: 99%
“…Demary (2008) confirmed the real interest level, together with the GDP, as the most important impact factors for property prices, while their impact weight differs throughout international comparisons. For instance, Berlemann and Freese (2010) argue that, for the specific case of Switzerland in the year 2010, commercial property prices showed no reaction towards a variation in the interest rate level. In a meta-study, Kuttner (2012) ultimately identified several reasons, how the interest rate does impact property prices, for instance due to changes in the willingness to take risks by investors or owners, but generally finds that the effect of the interest rate on house prices is rather moderate.…”
Section: Review Of Literaturementioning
confidence: 99%